PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING UNTUK MENINGKATAN HASIL BELAJAR EKONOMI PESERTA DIDIK KELAS XI SMA NEGERI 1 TOMA - Dao, Melinawati (LPPM Universitas Nias Raya, 2024)
This research aims to improve the learning outcomes of Economics among students of the eleventh-grade Social Sciences program at SMA Negeri 1 Toma through the implementation of the PBL cooperative learning model. The research method employed is action research involving 21 eleventh-grade Social Sciences students as the research subjects. The research is conducted in two cycles by collecting data through learning outcome tests, which are then analyzed using qualitative descriptive techniques. The results indicate that the implementation of the cooperative learning model effectively enhances students' learning outcomes significantly. The average learning outcomes of students increased from 76.77 in the first cycle to 82.97 in the second cycle, indicating an improvement of 6.22 points. This improvement reflects a significant enhancement in students' learning achievement from the category of fairly high in the first cycle to high in the second cycle. Consequently, it can be concluded that the application of the cooperative learning model has a positive impact on enhancing students' learning outcomes in Economics at SMA Negeri 1 Toma.